The Ilustation of Physical Health and Scizofrenia Patients’ Independence in Performing Personal Hygiene at Bali Province’s Mental Hospital - Desak Made Ari Dwi Jayanti; Dewa Putu Arwidiana (Universitas Respati Yogyakarta, 2020)
Not only mental problem do the schizophrenia patients suffer, but also physical problems. a quantitative descriptive with a cross-sectional approach model was hired in this research. This research employed 113 schizophrenia patients at the psykiatric hospital in Bali Province as samples with simple random technique. The instrument used to measure independence in performing personal hygiene was an observation sheet with Gordon's assessment scale and physical health assessment used an observation sheet, sphigmomanometer, scales and a meter to measure height. The results showed from the physical health assessment of the Body Mass Index in the most schizophrenia patients with a normal weight were 83 persons (73.5%), the thin patients were 12 persons (10.6%), More Body Weight were 5 persons (4.4%), obesity were 13 persons (11.5%), without concomitant diseases were 104 persons (92%), hypertension patient were 9 persons (8%). Independence in performing self-care were 69 respondents (61.1%) in the category of needing help, the majority of respondents were 79 respondents (69.9%), the category of needing assistance, self-care eating were 94 respondents (83.2%,) the category of needing help, toileting were 70 respondents (62.0%), Independence in performing personal hygiene was at 64 respondents (56.6%)